Generation Z’s Political Participation in the 2024 General Election: An Islamic Constitutional (Siyasah Dusturiyah) Perspective - Sarah Afifah; Nurul Nafsil Muthmainnah (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
Generation Z, as the largest demographic group in Indonesia, played a decisive role in the 2024 General Election. Their political participation reflects a new pattern influenced by digitalization and socio-political transformation. While most existing studies discuss Generation Z from the perspective of modern political science, little attention has been given to their role through the framework of Islamic constitutional law (siyasah dusturiyah). This study aims to analyze the political engagement of Generation Z in the 2024 election by contextualizing classical Islamic principles such as syura (consultation) and amar ma’ruf nahi munkar (enjoining good and forbidding evil) within a modern democratic setting. This research employs a qualitative normative-sociological approach. Primary data were obtained from reports of the General Election Commission (KPU), the Election Supervisory Agency (Bawaslu), and voter surveys, while secondary sources include classical fiqh siyasah, contemporary journals, and relevant media coverage. Data analysis applied a descriptive-analytical method combined with the maqāṣid al-syarī‘ah framework. Findings show that Generation Z demonstrated high voter turnout, strong engagement in digital activism, and issue-based preferences, prioritizing justice, environment, education, and healthcare over party loyalty. These behaviors align with siyasah dusturiyah values, framing elections as a modern form of syura to achieve just leadership. This study contributes theoretically by integrating Islamic constitutional thought with youth political participation, and practically by offering insights for policymakers, educators, and political actors to strengthen democratic participation rooted in justice and welfare.